2012
DOI: 10.3390/m780
|View full text |Cite
|
Sign up to set email alerts
|

2-(4-Diethoxymethylphenyl)-6-(4-nitrophenyl)-4-phenyl-1,3-diazabicyclo[3.1.0]hex-3-ene

Abstract: The photochromic compound was obtained from 4-diethoxymethyl-benzaldehyde and trans-2-benzoyl-3-(4-nitrophenyl)aziridine via a three component reaction. The structure of this compound was characterized by elemental analysis, 1H-NMR, 13C-NMR and UV-Visible spectral data

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
(45 reference statements)
2
4
0
Order By: Relevance
“…Similar to the recently published synthesis [31,32], to a magnetically stirred solution of trans-2-benzoyl-3-(4-nitrophenyl)aziridine 1 (0.268 g, 1 mmol) and 5-chloro-3-methyl-1-phenyl-1H-pyrazole-4-carbaldehyde 3 (0.221 g, 1 mmol) in 7 mL of absolute ethanol was added NH 4 OAc (0.78 g, 10 mmol) at room temperature. The mixture was stirred for 48 h. The reaction mixture was filtered, washed with absolute ethanol, dried under reduced pressure, and the resulting solid was recovered, purified by silica gel column chromatography using ethyl acetate/hexane (1:5, v/v) as the eluent, and recrystallized from absolute ethanol (10 mL) to give the target compound 7a as pale beige colorless solid that changed to the deep orange (7b).…”
Section: Synthesis Of 2-(5-chloro-supporting
confidence: 75%
“…Similar to the recently published synthesis [31,32], to a magnetically stirred solution of trans-2-benzoyl-3-(4-nitrophenyl)aziridine 1 (0.268 g, 1 mmol) and 5-chloro-3-methyl-1-phenyl-1H-pyrazole-4-carbaldehyde 3 (0.221 g, 1 mmol) in 7 mL of absolute ethanol was added NH 4 OAc (0.78 g, 10 mmol) at room temperature. The mixture was stirred for 48 h. The reaction mixture was filtered, washed with absolute ethanol, dried under reduced pressure, and the resulting solid was recovered, purified by silica gel column chromatography using ethyl acetate/hexane (1:5, v/v) as the eluent, and recrystallized from absolute ethanol (10 mL) to give the target compound 7a as pale beige colorless solid that changed to the deep orange (7b).…”
Section: Synthesis Of 2-(5-chloro-supporting
confidence: 75%
“…As expected, with increased irradiation time, intensity of the absorption band in the visible region is gradually increased, which states that the ring opening reaction occurs. These spectral changes showed that 4a exhibit photochromic behavior, similar to known triaryl-1,3-diazabicyclo[3.1.0]hex-3-enes [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Also, an isosbestic point at 270 nm showed the presence of two species 4a and 4b.…”
Section: Resultsmentioning
confidence: 90%
“…The 1 H-NMR spectrum of purified product showed signals belonging to one of the isomers. Based on chemical shifts of the H-2, H-5, and H-6 protons and compared them with those obtained by previously reported in the literature [19][20][21][22][23][24] suggests that endo-isomer of 4 is formed. Also, 13 C-NMR spectrum is in good agreement with the title compound.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations